Altitude Variation on Fruit Development and Quality Attributes of Kiwifruit (Actinidia Deliciosa Chev.) In North-Western Himalaya (Bangladesh Journal of Botany, 2023)
Effects of climatic variability at different altitudes on the fruit development and quality attributes of kiwifruit in the North -Western Himalayas of India were investigated. The experiment was carried out at five attitudinal locations (1090, 1275, 1425, 1543, and 1924 m above mean sea level) and with two cultivars viz. Hayward and Allison. It was observed that fruit yield and quality varied according to altitude and cultivars. The Hayward cultivar performed better in terms of yield, graded portion, and fruit quality like titratable acidity and ascorbic acid at higher elevations whereas, the Allison cultivar performed better at lower elevations. Findings revealed that the elevation ranging from 1000 to 1450 m was appropriate for the Allison cultivar and the elevation ranging from 1500 to 1950 m was appropriate for the Hayward cultivation.Bangladesh J. Bot. 52(2): 369-379, 2023 (June)